2019
DOI: 10.1002/adbi.201800328
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Mechanisms of Metastatic Cancer Cell Adhesive Phenotype Leveraging Preparative Adhesion Chromatography Microfluidic

Abstract: An integrated, parallel‐plate microfluidic device is engineered to interrogate and fractionate cells based on their adhesivity to a substrate surface functionalized with adhesive ligand in a tightly controlled flow environment to elucidate associated cell‐intrinsic pathways. Wall shear stress levels and endothelial presentation of E‐selectin are modeled after the inflamed vasculature microenvironment in order to simulate in vitro conditions under which in vivo hematogenous metastasis occurs. Based on elution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…High-speed videomicroscopy enabled visualization of cell adhesion of an infused cell pulse along the length of the divergent portion of the channel ( Figure 3 B), which was functionalized with adhesion receptors ( Birmingham et al., 2019 ; 2020 ; Edwards et al., 2018 ; Oh et al., 2015 ) to recapitulate their expression on the lymphatic endothelial cell-lined SCS floor ( Figure 3 C). The channel was also designed with a 10-cm long unfunctionalized portion ( Figures 3 A and 3B) sufficient in length to allow perfused cells to be uniformly in contact with the substrate, enabling all cells used in this work to settle to the channel bottom prior to reaching the functionalized section ( Birmingham et al., 2019 ). This design choice was made to ensure all perfused cells have uniform contact with the functionalized surface and thus the measured extents of adhesion are comparable between perfusion conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-speed videomicroscopy enabled visualization of cell adhesion of an infused cell pulse along the length of the divergent portion of the channel ( Figure 3 B), which was functionalized with adhesion receptors ( Birmingham et al., 2019 ; 2020 ; Edwards et al., 2018 ; Oh et al., 2015 ) to recapitulate their expression on the lymphatic endothelial cell-lined SCS floor ( Figure 3 C). The channel was also designed with a 10-cm long unfunctionalized portion ( Figures 3 A and 3B) sufficient in length to allow perfused cells to be uniformly in contact with the substrate, enabling all cells used in this work to settle to the channel bottom prior to reaching the functionalized section ( Birmingham et al., 2019 ). This design choice was made to ensure all perfused cells have uniform contact with the functionalized surface and thus the measured extents of adhesion are comparable between perfusion conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion by LS174T colon carcinoma cells, which are well studied for their adhesive properties within flow fields ( Birmingham et al., 2019 ; 2020 ; Erin E. Edwards et al., 2018 ; Oh et al., 2015 ) and express a variety of adhesion ligands for selectins ( Dallas et al., 2012 ; Hanley et al., 2006 ) and other CAMs ( Paschos et al., 2010 ), were evaluated ( Birmingham et al., 2019 , 2020 ; Dallas et al., 2012 ; Edwards et al., 2017 , 2018 ; Hanley et al., 2006 ; Thomas et al., 2008 ). Consistent with prior reports ( Fujisaki et al., 1999 ), LS174T cells did not adhere in flow to ICAM or VCAM ( Figures 4 D, 4H, and 4L) alone under any tested configuration of flow but interacted extensively with E-selectin ( Figures 4 A and 4C) at rolling velocities unchanged by flow condition ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…A flow-based microfluidic device was developed by Birmingham et al . to investigate metastasis via adhesion separation.…”
Section: Cell Separation Methodsmentioning
confidence: 99%
“…Residence time was used as a measure for cellular adhesive behavior to separate cells into two discrete fractions: adhesive and free-flowing. The device demonstrated that increased adhesion correlated with enhanced metastatic potential in LS174T colon carcinoma cells, affording the opportunity to better understand cancer metastasis …”
Section: Cell Separation Methodsmentioning
confidence: 99%
“…Both of these functionalities have recently been transferred to paper-based flow networks . Although numerous applications of these devices have been demonstrated, a major limitation of closed microfluidic systems is a lack of access to the surface, which significantly reduces applicability to biological substrates and surface bound species.…”
mentioning
confidence: 99%